ANALISIS KETIMPANGAN PEMBANGUNAN SEKTOR PETANIAN PADA WILAYAH DARATAN DI SULAWESI TENGGARA DENGAN PENDEKATAN INDEKS WILLIAMSON - Wa Ode Kuliati; Azhar Bafadal; Weka Gusmiarty Abdullah (Universitas Halu Oleo, 2018)
This study aims to analyze the level of inequality of agricultural development in the region of Southeast Sulawesi. The data used in this study is the type of secondary data that is time series and cross section (panel data), with period time of 2010-2015. Research variables consisted of GDP of agriculture sector, direct government expenditure, local income, and labor of agriculture sector, which then analyzed with Williamson Index approach. The results showed that the level of inequality of agricultural sector development in the mainland in Southeast Sulawesi (Konawe, Kolaka, Kendari, Konawe Selatan, Bombana, North Kolaka, North Konawe and East Kolaka) were generally high. This can be seen from the value of Williamson Index in 2010-2011 ranged from 0.4827 to 0.6607. Therefore, it is necessary to plan and policy in directing agricultural investment allocation towards a more balanced economic progress throughout the region.Keywords: Williamson index; high inequality; agricultural sector